Kazakhs and Siberian Cossacks in the Steppe Region: the Experience of Interethnic Interaction - Kapyshev, A.K.; Prokhorov, I.R.; Tuleuova, B.T.; Lebayev, F.R. (Bylye Gody, 2024)
The article deals with the formation, settlement and activity of the Siberian Cossack army in the territory of modern North-Eastern Kazakhstan in the XVIII-XIX centuries. The difficulties that the Siberian Cossacks faced in the region in ensuring their livelihoods in new natural conditions are shown. The real need for their peaceful and mutually beneficial interaction with the local Kazakh population is presented. Siberian Cossacks, actively borrowing the economic experience of nomads, in some cases introduced new models of economic activity, which were also in demand by Kazakhs. As a result of the economic interaction between Cossacks and Kazakhs, trade and the productive forces of the region are developing. The Siberian Cossacks were an instrument of Russian colonization, the guides of the policy of the Russian Empire. At the same time, they entered into peaceful relations with the local population. Such connections were often mutually beneficial. In general, it is necessary to note the important role of the Cossacks in the formation of agricultural culture, trade, industry, crafts and communication routes in the North-Eastern region of modern Kazakhstan. Despite the fact that the military settlers were burdened with government duties, they contributed to the development of the productive forces of the region, the introduction of new forms of management.
Keywords: Siberian Cossack army; “The Charter of the Siberian Kirghiz”; Kazakhs; Middle Zhuz; Omsk region; outer districts; Irtysh; Akmolinsk; Alexander I; interethnic interaction